Características pós-abate de novilhas terminadas em pastagem de Tifton 85 recebendo níveis crescentes de suplementação energética - Silva, Marcelo Ascoli da (2018)
The objective was to evaluate the effect of different levels of energy supplementation on carcass characteristics, meat quality and non integrant parts of carcass of heifers, finishing in Tifton 85 pasture. Thirty-two heifers slaughtered at 30 months of age were used, originating from the rotating crossing between the Charolais and Nellore breeds. The experimental design was completely randomized. The animals were distributed uniformly according to weight and genetic group at the following levels of supplementation: not supplemented; 0.4; 0.8 and 1.2 kg DM 100-1 kg body weight. Supplemented heifers, regardless of the level, presented higher slaughter weight, empty body weight and internal fat weight than heifers without supplementation. The hot and cold carcass weights, cold carcass yield, absolute weights of forequarter, sidecut, sawcut, muscle and fat, thickness of cushion, compactness of carcass, fat production in kg and the weight of were higher for heifers than 0.8 and 1.2%, compared to not supplemented. Higher muscle tissue weights were observed for 1.2%, in relation to not supplemented and 0.4%. Heart weight was higher for heifers fed 0.4 or 1.2%, in relation to not supplemented. Heifers with 1.2% of supplementation presented higher liver weight than those not supplemented. Heifers receiving 0.8% of supplementation presented higher values of L* and b* staining than heifers finished exclusively in Tifton 85 pasture. Higher levels of energy supplementation promote increases in the quantitative carcass traits of heifers, finishing in Tifton 85.